Meningkatkan Aktivitas dan Hasil Belajar Siswa Melalui Model Pembelajaran Koperatif Tipe Two Stay Two Stray pada Mata Pelajaran IPS (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This class action research aims to improve student learning outcomes in social studies learning through the cooperative model of two stay two stray type in class VII students of SMP Negeri 1 Limboto Barat. This type of research is classroom action research (PTK) while the approach uses a quantitative approach. This research was conducted at SMP Ngeri 1 Limboto Barat. The research subjects were the seventh grade students consisting of 27 students. This research was conducted in two cycles consisting of four competencies each cycle, namely planning, action, observation, and reflection. Data collection techniques used in this study include tests, and observation. The instruments used were tests, observation sheets. Based on the results of the research, it is known that through the cooperative learning model type two stay two stray has a positive and significant effect on learning outcomes from cycle I seen from the average value of the test of learning outcomes of students who reach completeness 70% while those who do not reach completeness 30% and in cycle II the learning outcomes of students who reach completeness 89% while the learning outcomes of students who have not completed 11%.